California Democratic Party Convention host hotel information (1991)
This packet provides logistical and procedural information for the California Democratic Party Convention held in Oakland, March 1–3, 1991. It outlines host hotel options, travel discounts, transportation arrangements, and car rental information, along with detailed convention rules governing delegates, resolutions, floor access, and proxy requirements. A tentative agenda lists registration, committee meetings, caucuses representing diverse constituencies, receptions, and party gatherings, reflecting the convention's organizational and political functions.